CX3CR1 deficiency delays acute skeletal muscle injury repair by impairing macrophage functions. Issue 1 (6th October 2015) - Zhao, Wanming; Lu, Haiyan; Wang, Xingyu; Ransohoff, Richard M.; Zhou, Lan
ABSTRACT: Adequate inflammatory response predominated by macrophage infiltration is essential to acute skeletal muscle injury repair. The majority of intramuscular macrophages express the chemokine receptor CX3 CR1. We studied the role of CX3CR1 in regulating intramuscular macrophage number and function in acute injury repair by using a loss‐of‐function approach. Muscle injury repair was delayed in CX3 CR1 GFP/GFP mice as compared with wild‐type (WT) controls. CX3 CR1 was predominantly expressed by macrophages but not by myogenic cells or capillary endothelia cells in injured muscles. Intramuscular macrophage number and subset composition were not altered by CX3 CR1 deficiency. Intramuscular macrophage phagocytosis function was impaired by CX3 CR1 deficiency as demonstrated by increased number of necrotic fibers (+115%) and percentage of necrotic area (+204%) at 7 d, increased number of intramuscular neutrophils at 3 (+89%) but not 1 d, reduced number of phagocytosing macrophages (–12%) and phagocytosed beads within macrophages (–15%) in CX3 CR1 GFP/GFP mice as compared with WT controls. The mRNA expression of CD36 (–50%), CD14 (–43%), IGF‐1 (–53%), and IL‐6 (–40%) was reduced in CX3 CR1‐deficient macrophages as compared with WT controls. We conclude that CX3CR1 is important to acute skeletal muscle injury repair by regulating macrophage phagocytosis function and trophic growth factor production.—Zhao, W., Lu, H., Wang, X., Ransohoff, R. M., Zhou, L. CX3 CR1 deficiency delays acute skeletal muscle injury repair by impairing macrophage functions. FASEB J. 30, 380‐393 (2016). www.fasebj.org